PARACOCCIDIOIDOMYCOSIS TREATMENT - SHIKANAI-YASUDA, Maria Aparecida (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
Considered to be an emerging endemic mycosis in Latin America, paracoccidioidomycosis is characterized by a chronic course and involvement of multiple organs in immunocompromised hosts. Infection sequelae are mainly related to pulmonary and adrenal insufficiency. The host-parasite interaction results in different expressions of the immune response depending on parasite pathogenicity, fungal load and genetic characteristics of the host. A few controlled and case series reports have shown that azoles and fast-acting sulfa derivatives are useful treatment alternatives in milder forms of the disease. For moderate/severe cases, more prolonged treatments or even parenteral routes are required especially when there is involvement of the digestive tract mucosa, resulting in poor drug absorption. Although comparative studies have reported that shorter treatment regimens with itraconazole are able to induce cure in chronically-infected patients, there are still treatment challenges such as the need for more controlled studies involving acute cases, the search for new drugs and combinations, and the search for compounds capable of modulating the immune response in severe cases as well as the paradoxical reactions.